Drying shrinkage in concrete assessed by nonlinear ultrasound. (February 2017) - Kim, Gun; Kim, Jin-Yeon; Kurtis, Kimberly E.; Jacobs, Laurence J.
Abstract: This research develops a nonlinear ultrasonic (NLU) technique, second harmonic generation (SHG), to monitor the time-dependent microstructural evolution and shrinkage in concrete over a period from 28 to 55 days of age. Drying shrinkage by moisture migration from concrete to its environment causes stress and microcracking and can lead to larger crack formation, which compromises performance. Here, the process of drying is monitored by the SHG method using nonlinear Rayleigh surface waves to obtain the acoustic nonlinearity parameter. The results show large changes in the measured acoustic nonlinearity parameter which is attributed to damage generated during drying shrinkage. Finally, the measured acoustic nonlinearity parameter is used to compare the microstructural condition in hardened concrete as affected by shrinkage mitigation (through the use of shrinkage-reducing admixture) and crack filling (or self-healing) by carbonation.